Diagnosis of Rheumatic Fever: Which Modification? - Bambang Madiyono; Sudigdo Sastroasmoro; Ismet N. Oesman; Sukman Tulus Putra; Najib Advani (Paediatrica Indonesiana, 1994)
We evaluated the implementation of diagnostic criteria on 547 ambulatory patients with rheumatic fever (RF) and rheumatic heart disease (RHD) between January 1, 1983 and December 31, 1992. The diagnosis of RF and reactive RHD was established by either revised Jones criteria, modified Jones criteria, or clinical judgment The patient's age ranged from 4-18 years, 255 (46.6%) of them were boys. The clinical manifestations found were fever (58.1 %), arthritis (41.9%), chorea (8.6%), subcutaneous nodule (1.3%), erythema marginatum (1.1%), holosystolic murmur (56.9%), mid-diastolic murmur (25.4%), and early diastolic murmur (29.5%). The laboratory changes were hemoglobin <10 g/dl (16.5%), BSR > 20 mm/h (56.30/o), ASTO >200 U (29.6%), PR interval> 0.16 sec (13.3%), and erR> 0.55 (27.6%). Revised Jones criteria were met in 162 cases (29%), modified criteria in 474 cases (86,6%), and clinical judgment in 521 cases (95.2%).